Evaluation of real estate investment projects with framework theory of real options: A case study in the shopping center project (Baghdad Mall) - هاشم, صبيحة قاسم; مكطوف, هنادي صكر (Journal of Economics and Administrative Sciences, 2016)
Focused research aims to provide a framework cognitive analytical nature of real estate investments and how they evaluated in the light of the assessment tools of modern theory of real options, and the possibility to rely on that theory in the detection of the true value of projects, real estate investments that would maximize the value of the investment decision taken, and the analysis of those projects that arise in the real estate markets and environments is the organization, which she was to make sure cases and high-risk, compared with entrances techniques, discounted cash flow (net present value). Based on the assumption lies in the possibility of the application of the implications of the theory of real options in evaluating real estate investments as input a complement to the entrance of the net present value, which would add value to these investments. Iraq and the fact that the real estate market is one of the markets with high dynamic, research has dealt him a sample assessment of real estate investment project being built in Iraq among several real estate investment projects are being built in Iraq represented a draft mall (Mall of Baghdad) to be applied in the analysis scope. The solution to the problem of search of the gap between the use of theoretical and practical implications of the theory of real options in the evaluation of projects, real estate investments, to reduce the risk and uncertain situations faced by investors as a result of investment in the real estate sector. Concluded the research that employ the theory of real options in evaluating the decision to project real estate investment, working to harness the resources of investment projects, not only to achieve a net present value is positive, but also help to generate multiple options and integrated future exceed the value of the net present value achieved, and that back at the end of ultimately to the creation of value-added withdraw to maximize the total value of the project. Find the need and recommended the adoption of the theory of real options is complementary input when evaluating projects, real estate investments, which are surrounded by cases of uncertain.